THE EFFECTIVENESS OF BHEE FRUIT (MELASTOMA Sp) WATER EXTRACT ON BLOOD GLUCOSE LEVELS - Rinawati; Sri Wahyuni Muhsin; Nasrianti Syam; Cukri Rahma (RADJA PUBLIKA, 2025)
Diabetes is a non-communicable disease with a prevalence that is increasing globally and nationally. Diabetes is characterized by blood glucose levels exceeding normal limits (>200 mg/dl). Blood glucose levels must be controlled to prevent serious complications in the human body. One method of controlling blood glucose levels is to use herbal medicines derived from plants. Exploration of herbal plants as antidiabetic agents remains limited. The Bhee fruit (Melastoma sp) is a widely distributed plant in Aceh, particularly in West Aceh, yet it has not been extensively utilized. The Bhee fruit holds potential as a herbal medicine; however, research confirming its antidiabetic properties remains scarce, necessitating further studies on its potential. This study aimed to determine the effectiveness of Bhee fruit water extract in lowering blood glucose levels in STZ-induced diabetic mice. The research method was a laboratory experiment using a completely randomized design. A total of 24 mice were divided into six groups with four replicates. The groups consisted of a normal control, a diabetic control, a drug control, a 100 mg/kg body weight extract dose, a 200 mg/kg body weight extract dose, and a 400 mg/kg body weight extract dose. The results showed that administration of Bhee fruit extract could lower blood glucose levels, particularly at the 400 mg/kg body weight dose.